1997
DOI: 10.1677/joe.0.1550401
|View full text |Cite
|
Sign up to set email alerts
|

Chorioamnionitis reduces placental endocrine functions: the role of bacterial lipopolysaccharide and superoxide anion

Abstract: Chorioamnionitis has been shown to be one of the most important factors in inducing preterm delivery. The present study was undertaken to examine the effects of chorioamnionitis on placental endocrine functions. Preterm placentas with histologic chorioamnionitis produced smaller amounts of human chorionic gonadotropin (hCG) and human placental lactogen (hPL) than those without chorioamnionitis (P < 0.001). To examine the mechanism involved in the suppression of placental endocrine functions induced by chorioam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…It has been suggested that increased ROS production triggers cellular antioxidant defence mechanisms, and up-regulation of MnSOD expression may be protective against cell injury caused by inflammation and oxidative stress[48,49]. Indeed, treatment with antioxidants can effectively block innate and adaptive immune responses through the following mechanisms: 1) inhibiting LPS-induced TLR-4 and NF-kB signaling and IL-8 transactivation[87]; 2) suppressing LPS-stimulated generation of proinflammatory cytokines (TNF-α, IL-1β) and ROS (NO2andnormalO2)[98]; 3) reducing cytotoxic T-cell response and allograft rejection[99]; or 4) generating antigen-specific hyporesponsiveness of T-cells[89].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that increased ROS production triggers cellular antioxidant defence mechanisms, and up-regulation of MnSOD expression may be protective against cell injury caused by inflammation and oxidative stress[48,49]. Indeed, treatment with antioxidants can effectively block innate and adaptive immune responses through the following mechanisms: 1) inhibiting LPS-induced TLR-4 and NF-kB signaling and IL-8 transactivation[87]; 2) suppressing LPS-stimulated generation of proinflammatory cytokines (TNF-α, IL-1β) and ROS (NO2andnormalO2)[98]; 3) reducing cytotoxic T-cell response and allograft rejection[99]; or 4) generating antigen-specific hyporesponsiveness of T-cells[89].…”
Section: Discussionmentioning
confidence: 99%
“…In this context is opportune to mention that LPS may affect indirectly the fetus through its action on placenta, *Address correspondence to this autho at the Department of Human Anatomy and Histology, University of Bari, P.zza G. Cesare, 11; I-70124 Bari, Italy; Tel: ++39-080-5478351; Fax: ++39-080-5478327; E-mail: ma.panaro@anatomia.uniba.it by promoting both ROS release from the neutrophils and monocytes of the organ [19] and the prostaglandins release [20]. In addition LPS may also affect directly the embryo since it is able to cross the placental barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Histologically demonstrated CA is reported to be associated with fetal growth retardation in term and preterm infants, presumably due to a reduction in placental hormone release [23,24].…”
mentioning
confidence: 99%